A methodology to assess mixer performance for selective catalyst reduction application in hot air gas burner - GÜL, MEHMET ZAFER (My University, 2022)
The active SCR aftertreatment system is one of the most crucial technology for the NOx reduction of diesel engines. One of the essential parameters of this technology is the urea spray performance on the catalyst.This study presents an experimental and numerical investigation of urea spray behavior used in the heavy-duty diesel engine\"s selective catalytic reduction (SCR) aftertreatment systems. The custom test rig is designed and built to simulate exhaust aftertreatment systems of heavyduty diesel vehicles. Urea injector parameters were observed in this test rig with optic windows for spray and flow visualization. This test rig is available to simulate diesel engines in the sense of exhaust mass flow rate, temperature and spray control unit. The discussion is made about the effects of droplet size of spray and velocity distribution upon flow characterization.A detailed assessment of the numerical model was presented, and validation was carried out for different interest measurement locations. The predicted droplet size distributions, breakup performance, and velocities are numerically and correlated with the experimental data. The validated model is subsequently used to study the urea-flow mixing dynamics to develop a urea mixer numerically. Test results show that smaller droplets enhance the mixing and thus catalyst efficiency. Mixer design performance can be assessed numerically in the droplet size break up based on the developed criteria called mixer performance criteria. Upstream and downstream of the mixer, droplet size can be extracted from the simulation, and different mixer designs can be compared in terms of the breakup performance.(c) 2021 THE AUTHORS. Published by Elsevier BV on behalf of Faculty of Engineering, Alexandria University. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/
Keywords: Harita Mühendisliği-Geomatik; Mühendislik ve Teknoloji; Geotechnical Engineering; Engineering and Technology; MÜHENDİSLİK, ÇOK DİSİPLİNLİ; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ENGINEERING, MULTIDISCIPLINARY; ENGINEERING; Engineering, Computing & Technology (ENG); General Engineering; Engineering (miscellaneous); Media Technology; Physical Sciences; NOx Reduction; Selective catalyst reduction; Spray; Droplet; UREA; INJECTION